AGS and NIA bench‐to bedside conference summary: Cancer and cardiovascular disease. Issue 10 (11th June 2022) - Mohile, Supriya; Blaum, Caroline S.; Abadir, Peter M.; Dale, William; Forman, Daniel E.; Fung, Chunkit; Holmes, Holly M.; Moslehi, Javid; Mustian, Karen M.; Rich, Michael W.; Whitson, Heather E.
Abstract: This report summarizes the presentations, discussions, and recommendations of the most recent American Geriatrics Society and National Institute on Aging research conference, "Cancer and Cardiovascular Disease, " on October 18–19, 2021. The purpose of this virtual meeting was to address the interface between cancer and heart disease, which are the two leading causes of death among older Americans. Age‐related physiologic changes are implicated in the pathogenesis of both conditions. Emerging data suggest that cancer‐related cardiovascular disease (CVD) involves disrupted cell signaling and cellular senescence. The risk factors for CVD are also risk factors for cancer and an increased likelihood of cancer death, and people who have both cancer and CVD do more poorly than those who have only cancer or only CVD. Issues addressed in this bench‐to‐bedside conference include mechanisms of cancer and CVD co‐development in older adults, cardiotoxic effects of cancer therapy, and management of comorbid cancer and CVD. Presenters discussed approaches to ensure equitable access to clinical trials and health care for diverse populations of adults with CVD and cancer, mechanisms of cancer therapy cardiotoxicity, and management of comorbid CVD and cancer, including the role of patient values and preferences in treatment decisions. Workshop participants identified many research gaps and questions that could lead to an enhanced understanding of comorbid CVD and cancer and to better and more equitable management strategies.